Psidium guajava Linn. extract mediated microwave synthesis and photocatalytic activities of ZnO nanoparticles - Somsri S. (2017)
© 2016 Elsevier B.V. All rights reserved. Crude water extract of Psidium guajava Linn. leaves was applied in the microwave synthesis of zinc oxide nanoparticles. The particles were characterized by transmission electron microscopy, selected area electron diffraction, powder X-ray diffraction, UV-vis and IR spectroscopies, thermogravimetry, and particle size and surface area analyses. The yielded particles are of hexagonal phase with 60-180 nm size distribution. The essential and functions of biomolecules in the extract and the influences of different zinc salts on the synthesis are presented. Photocatalytic activities were revealed to be excellent toward the degradation of methylene blue, methyl orange and orange II. The influences of the dyes' molecular structures on the degradation are discussed.